Nickel(ii) metal–organic frameworks with N, N′-di(4-pyridyl)-naphthalenediimide ligands: influence of secondary building unit geometry on dimensionality and framework dimensions. Issue 37 (5th September 2017) - Pfeiffer, Constance R.; Biggins, Naomi; Lewis, William; Champness, Neil R.
Abstract : The influence of intermolecular interactions and metal coordination geometry on MOF framework dimensions are discussed. Abstract : When Ni(NO3 )2 ·6H2 O and N, N ′-di(4-pyridyl)-1, 4, 5, 8-naphthalenetetracarboxydiimide (DPNDI) are reacted, a one-dimensional coordination polymer (1 ) is formed. However, analogous reactions with either terephthalic acid (2 ) or 2, 6-naphthalenedicarboxylic acid (3 ) and DPNDI affords two-dimensional, pillared metal–organic frameworks.2 and3 contain rectangular voids of different dimensions which are dictated by the carboxylate ligand and the arrangement of the {[M(k 2 -O2 NO)]2 (μ 2 -O2 CR)2 } secondary building unit (SBU) that forms the nodes of the framework. The role of SBU geometry, intermolecular face-to-face π–π and lone pair–π interactions involving the DPNDI ligands are discussed.